Restoring near-shore marine ecosystems to enhance climate security for island ocean states: Aligning international processes and local practices. (July 2018) - Wilson, A. Meriwether W.; Forsyth, Catherine
Abstract: This article contributes to a special issue examining SDG 14 and other international policy instruments for effective implementation of the Goal. This article focuses on island ocean states (IOS), or 'small island developing states' (SIDS), which are characterized by limited land and oceanic remoteness, creating local and international dependencies for food, livelihoods, trade and transport. While IOS contribute less than 1% to global green-house gases, they are directly impacted by extreme weather and climate change, in particular sea level rise. Near-shore marine ecosystems (mangroves, seagrasses and coral reefs) provide critical coastal protection and other benefits (e.g. fisheries), yet continue to be degraded from coastal development. Given their importance, restoration is needed where ecosystem function has declined, in concert with conservation of healthy sites. The overall restoration goals for IOS are to: i) enhance ecological integrity, ii) inspire local capacity building, and iii) accelerate climate change adaptation. This article examines the scope for such restoration through the UN SDGs, the Biodiversity Convention, the UN Framework Convention on Climate Change, and the Paris Agreement. Practical considerations of near-shore restoration are reviewed, emphasizing local and traditional knowledge regarding past and future perspectives. The article concludes with policy recommendations to integrate near-shore marine restoration across climate adaptation, conservation and planning processes to achieve synergies in effectiveness, essential to IOS settings. The UN SDGs provide a timely platform for IOS to align international processes with local needs to address their own goals in balancing population growth, economic development, food security and climate security. Highlights: Extreme weather, climate change, directly impacts island ocean states, SIDS. Near-shore mangroves, seagrasses, reefs, provide critical coastal protection. Restoration needed where ecosystem function lost, critical complement to MPAs. SDGs, biodiversity, climate adaptation plans effective marine restoration paths. Engage local, traditional stakeholders for long-term knowledge on climate change.